Toothbrushing wear resistance of stained cad/cam ceramics - Dal Piva, Amanda Maria de Oliveira [UNESP]; Bottino, Marco Antonio [UNESP]; Anami, Lilian Costa [UNESP]; Werner, Arie; Kleverlaan, Cornelis Johannes; Giudice, Roberto Lo; Famà, Fausto; Concilio, Laís Regiane da Silva; Tribst, João Paulo Mendes (MDPI, 2021)
Aim: To investigate the effect of toothbrushing on different stained Computerd Aided Design/Computer Aided Manufacturing CAD/CAM ceramics. Materials and Methods: Fifty specimens (high translucency zirconia, YZHT; zirconia-reinforced lithium silicate, ZLS; feldspathic, FDL; hybrid ceramic, HC; all from Vita Zahnfabrik) were divided into five groups according to their staining technique. ZLS allowed the composition of two groups: ZLS1 with crystallization and staining together; ZLS2, with the stain firing after the crystallization. YZHT received a stain firing after the sintering process, and FDL received stain firing directly. The HC was stained with acrylic stain-ing, and was light-cured on its surface. The specimens were brushed in total for 150,000 cycles at 2.45 N with 180 strokes/min. Surface measurements to obtain Rz were performed after 50,000, 100,000 and 150,000 cycles, with five evaluation lines (5 mm) per specimen orthogonal to the brushing direction, covering brushed and unbrushed areas. The wear was analyzed using two-way ANOVA and Tukey tests (α = 5%). Scanning electron microscopy (SEM) was performed to access the surface profile. The wear was affected by material (p < 0.001) and time (p = 0.139). Superior wear (µm) was observed for HC (6.6 ± 4.4; 6.8 ± 4.0; 9.2 ± 3.5) compared to ZLS2 (1.0 ± 0.3; 1.2 ± 2.2; 1.3 ± 0.3), YZHT (1.0 ± 0.1; 1.2 ± 0.3; 1.2 ± 0.3), ZLS1 (0.9 ± 0.1; 1.1 ± 0.5; 1.2 ± 0.3) and FDL (0.9 ± 0.1; 0.9 ± 0.1; 1.0 ± 0.2) after 5, 10 and 15 years of simulation, respectively. SEM showed different wear patters for HC with the removal of the glaze layer. HC showed a higher staining wear rate compared to the glass-based and polycrystalline ceramics after 15 years. The extrinsic characterization of feldspathic ceramic showed its superior longevity compared to the evaluated high-translucency zirconia, zir-conia-reinforced lithium silicate, and hybrid ceramic.
Keywords: Dental ceramics; Dental materials; Friction and wear; Toothbrushing; Wear depth